(untitled) (Journal of Architectural Design, 2023)
In the article, a program of conducting special experiments to determine the deformability and strength of the elements of the column made of fiber concrete was created. Based on the developed program, special experiments were conducted to determine the deformability and strength of the elements. The theoretical and practical results were compared.